2006
DOI: 10.1258/jrsm.99.2.81
|View full text |Cite
|
Sign up to set email alerts
|

Association of population and practice factors with potentially avoidable admission rates for chronic diseases in London: cross sectional analysis

Abstract: Although hospital admission for some chronic diseases is potentially avoidable and rates of hospital admission for these conditions are possible indicators of the quality of care, they should be interpreted in conjunction with measures of population composition and deprivation. Failure to do this may result in primary care trusts and general practitioners being criticized for aspects of health care utilization that are not under their direct control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 22 publications
(22 reference statements)
1
66
0
Order By: Relevance
“…Decreased socioeconomic status is consistently associated with increased ED attendance7 33 35 39 40 43 44 and increased EHA 8 16 17 21 22 25 36 45. A similar effect is seen with social isolation and lack of social support for ED attendance35 40 and EHA 8 35 41…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Decreased socioeconomic status is consistently associated with increased ED attendance7 33 35 39 40 43 44 and increased EHA 8 16 17 21 22 25 36 45. A similar effect is seen with social isolation and lack of social support for ED attendance35 40 and EHA 8 35 41…”
Section: Resultsmentioning
confidence: 98%
“…However, Cowling 2013 found no effect of the prevalence of asthma, obesity and hypertension in English practice on ED visits 39. Age-standardised patient increased mortality rates are also associated with increased EHA 8 35…”
Section: Resultsmentioning
confidence: 99%
“…32 Provision of diabetes clinics in primary care was significantly associated with reduced admission rates for diabetes, but the provision of asthma clinics was not associated with a similar reduction in admissions. 33 Conversely, a systematic review showed that high standards of diabetes care in primary care did not necessarily lead to reduced hospital admissions. 34 General practitioners are incentivised through the NHS Outcomes Framework to improve quality of care and outcomes for patients, with a stronger emphasis on mental health.…”
Section: Fundingmentioning
confidence: 99%
“…Many researchers have explored the factors affecting emergency admission rates overall, or for specific conditions, through studying variation between general practices in the UK [10][11][12][13][14][15][16][17][18][19] and internationally, 20 commissioning organisations in the UK 12,[21][22][23] or hospitals internationally. 24,25 Factors explaining variation were related to the population, particularly in terms of deprivation and health ( Table 1).…”
Section: Factors Affecting Emergency Admissionsmentioning
confidence: 99%